Molecular Cloning of Alternative Splicing Variants of the Porcine PML Gene and Its Expression Patterns During Japanese Encephalitis Virus Infection - Zhu, Jingjing; Chen, Zhenyu; Dai, Zhenglie; Zhou, Xiaolong; Wang, Han; Li, Xiangchen; Zhao, Ayong; Yang, Songbai (Frontiers in Veterinary Science, 2021)
Promyelocytic leukemia (PML) protein is a crucial component of PML-nuclear bodies (PML-NBs). PML and PML-NBs are involved in the regulation of various cellular functions, including the antiviral immune response. The human PML gene can generate several different isoforms through alternative splicing. However, little is known about the porcine PML alternative splicing isoforms and their expression profiles during Japanese encephalitis virus (JEV) infection. In the present study, we cloned seven mature transcripts of porcine PML, all of which contained the same N-terminal sequence but differed in the C-terminal sequences due to alternative splicing. These seven transcripts encoded five proteins all of which had the RBCC motif and sumoylation sites. Amino acid sequence homology analysis showed that porcine PML-1 had relatively high levels of identity with human, cattle, and goat homologs (76.21%, 77.17%, and 77.05%, respectively), and low identity with the mouse homolog (61.78%). Immunofluorescence analysis showed that the typical PML-NBs could be observed after overexpression of the five PML isoforms in PK15 cells. Quantitative reverse transcription PCR (RT-qPCR) analysis showed significant upregulation of PML isoforms and PML-NB-associated genes (Daxx and SP100) at 36 and 48 h post-infection (hpi). Western blotting analysis indicated that the PML isoforms were upregulated during the late stage of infection. Moreover, the number of PML-NBs was increased after JEV infection. These results suggest that porcine PML isoforms may play essential roles in JEV infection.